8(2x+3)-1=

Simple and best practice solution for 8(2x+3)-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(2x+3)-1= equation:


Simplifying
8(2x + 3) + -1 = 0

Reorder the terms:
8(3 + 2x) + -1 = 0
(3 * 8 + 2x * 8) + -1 = 0
(24 + 16x) + -1 = 0

Reorder the terms:
24 + -1 + 16x = 0

Combine like terms: 24 + -1 = 23
23 + 16x = 0

Solving
23 + 16x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + 16x = 0 + -23

Combine like terms: 23 + -23 = 0
0 + 16x = 0 + -23
16x = 0 + -23

Combine like terms: 0 + -23 = -23
16x = -23

Divide each side by '16'.
x = -1.4375

Simplifying
x = -1.4375

See similar equations:

| M-6+6=-2 | | -7-(-18)+(-10)= | | 27x^3+72x^2+48x=0 | | 1.9=2.9-0.2x | | (4x+1)+(6x-5)= | | -384=6(1-13x) | | 0.5*t=5*0.3 | | 5x(5x+3)=18 | | 6*0.5=-4(n-1) | | 0.25+15=7 | | -4x^2=224 | | .33+.66m=.66-.66 | | -1+21-40= | | 2x+9=25 | | 4p^2-8p=0 | | -58+35=x | | 16x=136 | | -161=7(-n-13) | | -(3-10y)= | | 1.5k=-20 | | -7(6x+3)= | | 2-0.75k=0.125+9 | | P-7=-8 | | 10x+45=20x-15 | | Y+8x=17 | | 30=7x+3-4 | | 5(4x-2)+9=2 | | 9x=36d | | (X)+3t-8y= | | n-38=18 | | 13=-2p+5 | | -4p^2=220 |

Equations solver categories